Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1440-1746.2008.05747.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic findings with symptom assessment systems (FSSG and QUEST) for gastroesophageal reflux disease in Japanese centres

Abstract: The FSSG score reflects the severity of the endoscopic findings of GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 29 publications
(61 reference statements)
1
51
1
Order By: Relevance
“…An investigation of the relationship between RE endoscopic findings and GERD symptoms also demonstrated that about 60% of RE relapsed cases had developed no GERD symptoms at the time of RE relapse. Several reports to date have also indicated that RE endoscopic findings were not accompanied by GERD symptoms (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and this trend was often found in elderly (28). It has also been reported that the percentage of severe RE is higher in the elderly than in juveniles, whereas the frequency of severe heartburn in patients with severe RE is lower in the elderly (27,36).…”
Section: Discussionmentioning
confidence: 91%
“…An investigation of the relationship between RE endoscopic findings and GERD symptoms also demonstrated that about 60% of RE relapsed cases had developed no GERD symptoms at the time of RE relapse. Several reports to date have also indicated that RE endoscopic findings were not accompanied by GERD symptoms (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and this trend was often found in elderly (28). It has also been reported that the percentage of severe RE is higher in the elderly than in juveniles, whereas the frequency of severe heartburn in patients with severe RE is lower in the elderly (27,36).…”
Section: Discussionmentioning
confidence: 91%
“…They reported that it showed a sensitivity of 62%, specificity of 59%, and accuracy of 60% when the c score was set at 8 points and F utoff SSG is widely used to evaluate GERD symptoms thereafter [13][14][15]. In this study, mean score of FSSG before starting the program was 8.6 and 30% of patients was equal or more than 8 points.…”
Section: Discussionmentioning
confidence: 87%
“…In patients with GERD, the FSSG score could be used to not only diagnose GERD but also assess the efficacy of PPI treatment for GERD [5].The symptom improvement rate of RPZ10mg daily dosing was 69.9% (107/153), a relatively favorable rate. No significant differences were observed between the prompt PPI treatment group (80.0%, 16/20) and the prompt endoscopy group (68.4%, 91/133)(p=0.43).However, performing prompt endoscopy can exclude malignant disorders and enable the diagnosis of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with scores≧ 8 were diagnosed with GERD. Symptom improvement was defined as scores of FSSG < 8 or ≧50% score reduction after dosing [5]. Each dropout stage on GERD-GL flowchart was defined as: stage 1; the patients couldn't be evaluated symptoms improvement after prompt PPI treatment; stage 2; the patients didn't visit hospital/clinic before PPI treatment on prompt endoscopy group; stage 3: the patients couldn't be followed up to long-term management after symptoms improvement on prompt endoscopy; stage 4;the patients didn't visit hospital/ clinic despite persisting symptoms after PPI treatment or were treated by the optional treatments; stage 5;PPI refractory GERD patients couldn't be followed up to long-term management after pathophysiologic evaluation (e.g.…”
Section: Methodsmentioning
confidence: 99%